The complete chloroplast genome sequence of sugar beet (Beta vulgaris ssp. vulgaris). (June 2014) - Li, Han; Cao, Hua; Cai, Yan-Fei; Wang, Ji-Hua; Qu, Su-Ping; Huang, Xing-Qi
Abstract The complete nucleotide sequence of the sugar beet (Beta vulgaris ssp. vulgaris) chloroplast genome (cpDNA) was determined in this study. The cpDNA was 149, 637 bp in length, containing a pair of 24, 439 bp inverted repeat regions (IR), which were separated by small and large single copy regions (SSC and LSC) of 17, 701 and 83, 057 bp, respectively. 53.4% of the sugar beet cpDNA consisted of gene coding regions (protein coding and RNA genes). The gene content and relative positions of 113 individual genes (79 protein encoding genes, 30 tRNA genes, 4 rRNA genes) were almost identical to those of tabacoo cpDNA. The overall AT contents of the sugar beet cpDNA were 63.6% and in the LSC, SSC and IR regions were 65.9%, 70.8% and 57.8%, respectively. Fifteen genes contained one intron, while three genes had two introns.